The grammar of Q Q-particles, WH-movement, and pied-piping - Cable, Seth. (New York ; Oxford : Oxford University Press, 2010)
'The Grammar of Q' puts forth a novel syntactic & semantic analysis of wh-questions, based on an in-depth study of the Tlingit language, an endangered & under-documented Native American tongue. A major conclusion is that the phenomenon classically dubbed 'pied-piping' does not actually exist.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Grammar, Comparative and general -- Interrogative; Grammar, Comparative and general -- Word order; Grammar, Comparative and general -- Syntax; Tlingit language; Minimalist theory (Linguistics)